Answer:
(2,1)
Explanation:
So the first thing you want to do is substitute. You want to plug in the equation for y in for the y value above.
So you would do 3x+4(x-1)=10. As you can see we took the bottom equation and put it in for the top equation. We did this so we only have x s and no y s.
Now you would solve. You would distribute first. You would get 3x+4x-4=10. Now combine like terms. 3+4 is 7 so you would get 7x-4=10.The next thing you want to do is get the 7x by itself so move the 4.You would get 7x=14. Now divided both sides by 7 because you want to get the x by itself.
You would get x=2. Now for the y value just plug it in for an equation above. The easier one would be y=x-1. y=(2)-1 will equal 1. You write your final answer in (x,y) style. Your final answer will then be (2,1)